Dry permafrost over ice-cemented ground at Elephant Head, Ellsworth Land, Antarctica. Issue 5 (October 2019) - McKay, Christopher P.; Balaban, Edward; Abrahams, Simon; Lewis, Nick
Abstract: Dry permafrost - ground with temperature always below 0°C and containing negligible ice - overlying ice-cemented ground has been reported in the Dry Valleys of Antarctica and on Mars. Here we report on a new site (79°49.213'S, 83°18.860'W, 718 m elevation) located on the side of Mount Dolence in Ellsworth Land, Antarctica. Year-round temperature and humidity measurements indicate that dry permafrost is present between depths of 13.5 and 49.0 cm - the location of ice-cemented ground. The mean annual frost point of the ice-cemented ground is -17.0 ± 0.2°C and the mean annual frost point of the atmosphere is -22.7 ± 1°C. The corresponding mean annual temperatures are -19.2°C and -20.3°C. Neither the temperature of the ice-cemented ground nor the air rise above freezing. Both the dry permafrost and the ice table may be habitable. In the dry soil at 3 cm depth there are 80 hours in the summer when temperature exceeds -5°C and water activity exceeds 0.8. At the ice table, temperature exceeds -10°C and water activity exceeds 0.8 for 35 hours in the year. The ice table and the dry permafrost above it would be considered a 'Special Region' on Mars. Further microbial investigation of this site is indicated.